Indeterminacy and Interview Research: Co-Constructing Ambiguity and Clarity in Interviews with an Adult Immigrant Learner of English - Miller, Elizabeth R (Applied linguistics, 2011)
This article adopts a social constructionist approach in maintaining that indeterminacy of meaning is an unavoidable aspect of interview research. It uses positioning analysis to examine how subject positions and contingently constructed meanings are produced in interview interactions. The analysis focuses on excerpts from a series of three interviews with a Chinese-born immigrant to the US in which the interviewee responds to questions asking whether he has experienced discrimination. The interviewee produces accounts that are seemingly ambiguous at times and seemingly clear on another occasion. Rather than determining exactly what he means across these three accounts, the article uses fine-grained micro-analysis to examine the linguistic constructs and interactional strategies used to construct such ambiguity and clarity. It also examines the role of the researcher in contributing to such interpretations given her projection of the "imagined subject" who is producing these accounts. The article concludes with a discussion of the agentive subjectivity constituted for interviewees through the interview process, which contributes to the indeterminacy of meaning true for all interview research.